2016 Intl IEEE Conferences on Ubiquitous Intelligence &Amp; Computing, Advanced and Trusted Computing, Scalable Computing and C 2016
DOI: 10.1109/uic-atc-scalcom-cbdcom-iop-smartworld.2016.0059
|View full text |Cite
|
Sign up to set email alerts
|

VIPR: A Visual Interface Tool for Programming Semantic Web Rules

Abstract: Abstract-Semantic technologies have evolved from the initial purpose of supporting semantic integration and information exchange for the semantic web, towards a generic set of engineering tools for knowledge modelling, representation and inference. However, there is still much work required within the area of Semantic computing and the area highlights a key research challenge involving the complexity in engineering Semantic rules and associated dedicated models. Many existing tools focus on the creation of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These rules are designed to obtain the desired outcome based on already stored facts meeting several conditions and adds more power to OWL capabilities for deductive reasoning. Integration of SWRL to ontological based inferring systems have shown their importance for context-aware applications [ 41 ]. Ontological models have limitations for handling complex rules as in our case fusing multi-level cross-domain contexts, which are discussed in subsequent sections.…”
Section: Context Reasoningmentioning
confidence: 99%
“…These rules are designed to obtain the desired outcome based on already stored facts meeting several conditions and adds more power to OWL capabilities for deductive reasoning. Integration of SWRL to ontological based inferring systems have shown their importance for context-aware applications [ 41 ]. Ontological models have limitations for handling complex rules as in our case fusing multi-level cross-domain contexts, which are discussed in subsequent sections.…”
Section: Context Reasoningmentioning
confidence: 99%
“…In the light of survey results, giving user control in a context aware application is appreciated by most of the users. [26] suggested that giving 100 % self adaptivity to context aware application may make its users anxious. While there has been intensive research on contextawareness and a summary of contributions made in this field can be found at [6], [1], the research on providing user control in context-aware application has just started getting attention from research community.…”
Section: Introductionmentioning
confidence: 99%